(untitled) (Tanzania Medical Journal, 2017)
UHQ, a four -month-old female child, was rushed to the Emergency Medicine Department (EMD) due to severe spontaneous bleeding. This exclusively breast fed child had a history of diarrhea, vomiting and taking broad-spectrum antibiotics over the last two weeks. She developed nodular purpuric spots for about three days prior to the intracranial bleeding. She was unconscious and responding only to pain, and was severely pale. She was transfused with two units of whole blood and underwent a craniotomy for draining the hemorrhage. She was treated with Vitamin K supplements. Her OFC was 44cm on admission. She was discharged after one week, with OFC 41cm. On follow-up, she is developing normally.